The impact of preformed donor‐specific antibodies in living donor liver transplantation according to graft volume. Issue 3 (22nd January 2022) - Goto, Ryoichi; Ito, Makoto; Kawamura, Norio; Watanabe, Masaaki; Ganchiku, Yoshikazu; Kamiyama, Toshiya; Shimamura, Tsuyoshi; Taketomi, Akinobu
Abstract: Introduction: The roles of preformed anti‐HLA donor‐specific antibodies (DSAs) in liver transplantation remain controversial. We evaluated the impact of preformed DSAs in living donor liver transplantation. Methods: Adults who underwent living donor liver transplantation ( n  = 175) in our institute were included in this study. Lymphocyte cytotoxicity test (LCT), flow cytometric crossmatch (FCXM), and single‐antigen bead assays were performed. Results: Among adult living donor liver transplantation recipients, 27 (16.5%) and 14 (8.5%) had pretransplant FCXM‐positive findings and LCT‐positive findings, respectively. FCXM‐positive patients displayed a significantly worse 5‐year graft survival rate (77.3%; vs. DSA‐negative, 91.6%). Six of 14 LCT‐positive patients exhibited graft loss shortly after transplantation (5‐year survival rate: 57.1%). All LCT‐positive patients with graft loss underwent left lobe living donor liver transplantation. Significantly lower ratio of graft volume relative to standard liver volume (32.9 ± 5.7%) and smaller graft size (365.3 ± 57.9 g) were observed in patients with graft loss ( p  < .03, vs. surviving grafts). Significantly higher DSA‐mean fluorescence intensity (MFI) values were present in patients with graft loss ( p  = .0012, vs. surviving grafts). Conclusions: Patients with preformed DSAs exhibited worse graft outcomes in living donor liver transplantation. Higher DSA‐MFI values and smaller graft size were associated with worse outcomes in LCT‐positive patients. High‐risk patients with preformed DSAs should be considered for appropriate graft selection and application of a desensitization protocol. Abstract : This study highlights the clinical impact of preformed donor‐specific antibodies (DSA) in living donor liver transplantation. We interestingly showed that the graft volume is an important risk factor in highly DSA‐mean fluorescence intensity (MFI) cases. An appropriate graft selection should be carefully considered in high‐risk case with preformed DSA in living donor liver transplantation